(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article highlights the formation of the income base of local budgets, the importance and scientific and practical basis of land tax and property tax. Local budgets are based on opportunities to ensure income stability. Procedures and practical recommendations were proposed to increase the importance of land and property taxes in the formation of income of local budgets. In addition, a study was carried out on ways to increase the income of the local budget, within the framework of which the research of economic scientists was studied, conclusions and proposals were formed.